Right putamen hemorrhage manifesting as apraxia of eyelid opening - Lin YH (Dove Medical Press, 2013)
Yi-Hui Lin,1 Li-Min Liou,2,3 Chiou-Lian Lai,1,2 Yang-Pei Chang1,2 1Department of Neurology, Kaohsiung Medical University Hospital, 2Department of Neurology, Faculty of Medicine, College of Medicine, Kaohsiung Medical University, 3Department of Neurology, Kaohsiung Municipal Hsiao-Kang Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan Purpose: The purpose of this report is to demonstrate a rare clinical manifestation of apraxia eyelid opening related to a basal ganglia lesion. Case report: In this study, we report a 91-year-old woman suffering from difficulty in eyelid opening after being treated for myocardial ischemia with dual antiplatelet medications. She could open her eyelid with fingers touching her forehead. Brain computed tomography revealed a right putamen hemorrhage. Surface electromyography revealed persistent frontalis muscle contraction during relaxation of orbicularis oculi muscles. Apraxia of eyelid opening was diagnosed. Her eyelid symptom resolved 2 months later. Conclusion: Apraxia of eyelid opening may be caused by subcortical hemorrhage of the basal ganglia. In addition to the primary motor cortex and supplemental motor area, the basal ganglia may also play a role in eyelid opening. Keywords: intracranial hemorrhage, basal ganglia, orbicularis oculi muscle, frontalis muscle